Investigating the Wear Behaviour of FeCrC/B4C Powder Alloys Coating Produced by Plasma Transferred Arc Weld Surfacing Using the Taguchi Method - Gur, Ali Kaya (Carl Hanser Verlag, 2013)
In this study, the optimization of the abrasive wear behaviour of a medium carbon steel surface with a FeCrC/B4C powder coating applied by using the plasma arc weld surfacing process is examined. Optimization of the process parameters represents the key step in the Taguchi method to achieve high quality without increasing cost. The Taguchi method uses orthogonal arrays to maximize the effect of controllable parameters and to minimize the effect of uncontrollable process parameters. The abrasive wear behaviour of the surface of a medium carbon steel substrate material coated with FeCrC and with 15% or 25 % B4C was tested at loads of 10 N, 20 N, and 30 N and at distances of 10 m, 20 m, and 30 m. The lowest wear loss, representing the most important criterion in determining the wear behaviour, was optimized with the so-called lowest-the best control characteristics of the Taguchi method and the results were analyzed by graphical methods.
Keywords: Steel; Resistance; Microstructure; Composite